Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jtcvs.2017.08.116
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical intervention for anomalous aortic origin of a coronary artery: A large contemporary prospective cohort study

Abstract: Surgical treatment for anomalous aortic origin of a coronary artery is safe and should aim to associate the coronary ostium with the correct sinus, away from the intercoronary pillar. After surgery, the majority of patients are cleared for exercise and remain asymptomatic. Longer follow-up is needed to assess the true efficacy of surgery in the prevention of sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 32 publications
4
71
0
1
Order By: Relevance
“…Surgical treatment has been widely proposed, aiming at removing any risk of myocardial ischemia and SCD. Single-center studies are based on limited series describing surgical repair as safe and effective [7][8][9][10][11][12][13], although late effects on symptoms and risk of SCD are undefined and concerns about the surgical effectiveness remain [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment has been widely proposed, aiming at removing any risk of myocardial ischemia and SCD. Single-center studies are based on limited series describing surgical repair as safe and effective [7][8][9][10][11][12][13], although late effects on symptoms and risk of SCD are undefined and concerns about the surgical effectiveness remain [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Mery et al have recently reported their experience with 44 patients who underwent surgical intervention for AAOCA over a 4½‐year time period . These 44 patients were part of a large, prospective cohort study in which all of the patients had extensive and comprehensive testing.…”
Section: Discussionmentioning
confidence: 99%
“…Single-centre studies report on limited series, describing surgical repair as safe and effective [6][7][8][9][10][11][12], although late effects on symptoms and risk of SCD are undefined and concerns about the surgical effectiveness remain [13][14][15].…”
Section: Introductionmentioning
confidence: 99%